Genome-Wide Analysis of microRNA and mRNA Expression in Colorectal Intramucosal Neoplasia and Colorectal Cancer With a Microsatellite-Stable Phenotype Based on Adenoma-Carcinoma Sequences - Sugai, Tamotsu; Osakabe, Mitsumasa; Niinuma, Takeshi; Sugimoto, Ryo; Eizuka, Makoto; Tanaka, Yoshihito; Yanagawa, Naoki; Otsuka, Koki; Sasaki, Akira; Matsumoto, Takayuki; Suzuki, Hiromu (Frontiers in Oncology, 2022)
Background: Although MicroRNAs (miRNAs) play important roles in various biological processes, the biological functions of miRNAs are achieved through mRNAs. The aim of this study is to identify dysregulated miRNA/mRNA expression patterns in colorectal tumors. Methods: We examined 42 colorectal tumors (15 adenomas, 8 intramucosal cancers [IMCs], and 19 invasive colorectal cancers [CRCs]) with the microsatellite stable (MSS) phenotype (first cohort). The first cohort was used for genome-wide miRNA and mRNA expression arrays, whereas the second cohort (37 colorectal neoplasias) was used for validation analyses. Finally, we used 15 cases of “adenoma in/with carcinoma” to identify network patterns of miRNAs/mRNAs that were directly associated with neoplastic progression. In addition, simple regression analysis for array-based and RT-PCR analyses was performed to select candidate miRNA–mRNA pairs. Transfection of miRNA mimics was also performed to confirm whether target mRNA expression is affected by specific miRNAs. Results: Specific paired miRNA/mRNA networks, including hsa-miR-34a-5p/SLC12A2, hsa-miR-15b-5p/SLC12A2, hsa-miR-195-5p/SLC12A2, hsa-miRNA-502-3p/OLFM4, hsa-miRNA-6807-5p/ZG16, and hsa-miRNA 3064-5p/SH3BGRL3, were identified in samples of adenoma, IMC, and CRC with the MSS phenotype. In adenomatous lesions obtained from the same tumor with a carcinomatous lesion, we identified pairs of miRNA-130a-3p/HSPA8 and miRNA-22-3p/RP53 that were linked to multiple pathways. On the other hand, 2 pairs of miRNA/mRNA (miRNA-660-5p and miRNA-664a-5p/APP) were found in isolated carcinomatous glands. Ectopic expression of miRNA 3064-5p suppressed SH3BGRL3 expression. Conclusions: We found that networks based on specific pairs of miRNAs/mRNAs contribute to progression from adenomatous and carcinomatous lesions. Our results provide insights into the molecular tumorigenesis of colorectal tumors.